Extending Continental Lithosphere With Lateral Strength Variations: Effects on Deformation Localization and Margin Geometries - Beniest, Anouk; Willingshofer, Ernst; Sokoutis, Dimitrios; Sassi, William (Frontiers in Earth Science, 2018)
We investigate the development of margin geometries during extension of a continental lithosphere containing lateral strength variations. These strength variations may originate from the amalgamation of continents with different mechanical properties as was probably the case when Pangea was assembled. Our aim is to infer if localization of deformation is controlled by the boundary between two lithospheres with different mechanical properties (e.g. ‘weak’ and ‘strong’) or not. We ran a series of lithosphere-scale physical analogue models in which we vary the strength contrast across equally sized lithospheric domains. The models show that deformation always localizes in the relatively weaker compartment, not at the contact between the two domains because the contact is unfavorably oriented for the applied stress and does not behave as a weak, inherited discontinuity. Wide-rifts develop under coupled conditions when the weak lithosphere consists of a brittle crust, ductile crust and ductile mantle. When a brittle upper mantle layer is included in the weak segment, the rift system develops in two phases. First, a wide rift forms until the mechanically strong upper mantle develops a necking instability after which the weak lower crust and weak upper mantle become a coupled, narrow rift system. The margin geometries that result from this two-phase evolution show asymmetry in terms of crustal thickness and basin distribution. This depends heavily on the locus of failure of the strong part of the upper mantle. The models can explain asymmetric conjugate margin geometries without using weak zones to guide deformation localization.